An investigation of two methods of DNA recovery from fired and unfired 9 mm ammunition. Issue 2 (March 2021) - Moore, David; Beaumont, Dan; Brown, Melanie; Clayton, Tim; Coleman, Kiera; Subhani, Zuhaib; Thomson, Jim
Highlights: Improved STR profiles are obtained from 9 mm ammunition using a direct lysis method. Successful STR profiling was achieved from both fired and unfired 9 mm cartridges. For most samples the major profile observed matched the known handler. 56% of profiles obtained from the direct lysis method produced LRs >1 million. Abstract: Cartridge cases are often recovered from crime scenes involving firearms and, in the United Kingdom (where gun possession is strictly controlled), these are commonly from 9 mm calibre ammunition. The ability to obtain informative DNA profiles from touch DNA on recovered cartridges could have a significant impact on the investigation of that type of offence. However, this avenue may not be routinely considered as investigators in the UK have historically had a low expectation of obtaining useful DNA profiles. This stance may not be unreasonable given that (a) only trace amounts of DNA are likely to have been transferred onto the cartridge cases through handling; and (b) when the cartridge is spent, the potential deterioration of that DNA caused by the act of discharging the weapon. We introduce a novel semi-automatable method using direct lysis for the recovery of DNA from ammunition and compare it with a traditional double-swabbing method (using wet and dry swabs). DNA profiling of the DNA recovered using both methods was carried out using the ESI17 FAST STR system (Promega). This demonstrated a significant increase in DNA recovery using the direct lysis approach, and correspondingly improved STR results. We also investigated the effect on the recovery and profiling of DNA from fired, and unfired, 9 mm cartridges using the direct lysis technique. These results demonstrate that DNA suitable for STR analysis can still be recovered from fired ammunition with only slightly reduced yields compared to unfired ammunition. In these experiments, the handler of the ammunition was most commonly either the sole contributor or the major contributor to the recovered DNA profile.